2019
DOI: 10.3390/nano9040639
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impact of Cross-Polymerization on the Structural and Frictional Properties of Alkylsilane Monolayers Using Molecular Simulation

Abstract: Cross-linked chemisorbed n-alkylsilane (CH3(CH2)n−1Si(OH)3) monolayers on amorphous silica surfaces have been studied and their structural properties and frictional performance were compared to those of equivalent monolayers without cross-linkages. The simulations isolated for the first time the effects of both siloxane cross-linkages and the fraction of chains chemisorbed to the surface, providing insight into a longstanding fundamental question in the literature regarding molecular-level structure. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…However, only few MD simulations studies have addressed these questions. Different MD studies suggested that the order parameter of n -alkylsilane monolayers (for n > 8) increases as the alkyl chain length and the surface coverage increase, while alkyl chain tilt angles are independent of chain length and decrease as surface coverage increases. Among them, it was also shown that perfluorodecyltrichlorosilane (FDTS) monolayers at high surface coverage present a hexagonal packing, whereas such packing was attenuated for octadecyltrichlorosilane (OTS) monolayers for the same surface coverage . In the present study, we demonstrate an effect of the head-group charge and alkyl chain length ( n < 18), on the organization of the monolayer.…”
Section: Introductionsupporting
confidence: 54%
“…However, only few MD simulations studies have addressed these questions. Different MD studies suggested that the order parameter of n -alkylsilane monolayers (for n > 8) increases as the alkyl chain length and the surface coverage increase, while alkyl chain tilt angles are independent of chain length and decrease as surface coverage increases. Among them, it was also shown that perfluorodecyltrichlorosilane (FDTS) monolayers at high surface coverage present a hexagonal packing, whereas such packing was attenuated for octadecyltrichlorosilane (OTS) monolayers for the same surface coverage . In the present study, we demonstrate an effect of the head-group charge and alkyl chain length ( n < 18), on the organization of the monolayer.…”
Section: Introductionsupporting
confidence: 54%
“…Although the enhancement of the electrokinetic transport over concentrated brush-like PELs has not been validated by experimental measurements, it is well known that high packing densities are crucial for the tribological performance of monolayers. 71–73 Our theoretical work suggests that densely packed monolayers can enhance electrokinetic transport and encourages further experimental studies.…”
Section: Discussionmentioning
confidence: 63%
“…According to the experimental results, the atomic models of self-assembled molecules on the insert surface were built. The adsorption behaviors of different interfaces were investigated by MD method [ 23 , 24 , 25 ]. Moreover, the anti-adhesion mechanisms of the polymer-alkanethiols interface in different arrangements were explored by analyzing the morphological evolution, potential energy, interaction energy, adhesion work and the radial distribution function at the interface comprehensively.…”
Section: Introductionmentioning
confidence: 99%